The Psychology of Couples and Illness: Theory, Research, &Amp; Practice. 2000
DOI: 10.1037/10360-006
|View full text |Cite
|
Sign up to set email alerts
|

Couples with HIV/AIDS.

Abstract: Couples affected by AIDS face a plethora of challenges, some of which are common to many life-threatening illnesses and others of which are unique to AIDS. HIV infection is in many ways a disease of couple relationships. Today, nearly all adults living with HIV infection in industrialized nations became infected with the virus through interpersonal relations, by either a sexual or syringe-sharing partner. In many cases, the relationship within which a person became HIV infected dissolves, only to be followed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Kalichman (2000) proposed that one explanation for the finding that HIV-infected men and women in relationships reported significantly less symptoms of somatic distress than those without partners, was that the partner-relationship might buffer and thus offer some protection from the emotional distress of living with HIV by providing both tangible and emotional social support (Kalichman, 2000). This study suggests the picture is more complex, and that the benefits provided by a partner-relationship may not necessarily be in the form of tangible or emotional support.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Kalichman (2000) proposed that one explanation for the finding that HIV-infected men and women in relationships reported significantly less symptoms of somatic distress than those without partners, was that the partner-relationship might buffer and thus offer some protection from the emotional distress of living with HIV by providing both tangible and emotional social support (Kalichman, 2000). This study suggests the picture is more complex, and that the benefits provided by a partner-relationship may not necessarily be in the form of tangible or emotional support.…”
Section: Discussionmentioning
confidence: 97%
“…One empirical study, by Kalichman (see Kalichman, 2000) found that HIV-infected men and women in relationships reported significantly fewer symptoms of somatic distress than those without partners. A suggested explanation for this was that the partner-relationship might buffer and thus offer some protection from the emotional distress of living with HIV by providing both tangible and emotional social support.…”
Section: Chronic Illness Hiv Infection and Partner Relationshipsmentioning
confidence: 98%
“…Over the years, they have identified links between unprotected sex and, for example, an absence of illness symptoms (Skurnick et al 1998), greater HIV optimism (van de Ven et al 2005, the impact of an undetectable viral load on perceptions of infectivity (van de Ven et al 2005), duration of the relationship (Milam et al 2006), lower depression scores (Bradley et al 2008), lower education levels, unemployment and drug use (Buchacz et al 2001), lack of condom availability (Lau et al 2012), negative attitudes to condoms (Israel et al 2005), and refusal by male partners to use condoms (Semple et al 2002, Dave et al 2006, Milam et al 2006, Peretti-Watel et al 2006, Stevens and Galvao 2007. Some studies have also observed that HIV-negative partners tend to be the primary initiators of unprotected sex ( Van der Straten et al 1998, Kalichman 2000, Palmer and Bor 2001, and that repeated negative HIV tests for the uninfected partner reinforce a sense of low risk ( Van der Straten et al 1998, Persson and Richards 2008a, Reis and Gir 2009. Overall, the research findings are so mixed and contradictory that this, in itself, suggests that a range of complex factors are at play in serodiscordant relationships (Crepaz and Marks 2002), which in turn raises questions around how HIV 'risk' is defined and whether it means the same in all settings.…”
Section: Introductionmentioning
confidence: 93%
“…The small body of literature that goes beyond risk to explore the experiences of serodiscordance tends to focus on tensions in such relationships, describing how couples struggle with numerous social, sexual, and emotional challenges and stressors (Kalichman 2000;VanDevanter et al 1999;Van der Straten et al 1998;Jarman, Walsh, and De Lacey 2005;Pomeroy, Green, and Van Laningham 2002;Knight et al 1997;Moore et al 1998;Remien et al 2003;Palmer and Bor 2001). The word itself, discordance, suggests disharmony and friction.…”
Section: Enacting Hiv-negativity: a Look At The Social Research Litermentioning
confidence: 96%